Gluten-free diet in children with recent-onset type 1 diabetes: A 12-month intervention trial - Neuman, Vit; Pruhova, Stepanka; Kulich, Michal; Kolouskova, Stanislava; Vosahlo, Jan; Romanova, Martina; Petruzelkova, Lenka; Obermannova, Barbora; Funda, David P; Cinek, Ondrej; Sumnik, Zdenek (Diabetes, obesity & metabolism, 2020)
AIM: To test whether a gluten-free diet (GFD) is associated with the deceleration of the decline in beta-cell capacity in non-coeliac children with recently diagnosed type 1 diabetes. METHODS: Forty-five children (aged 10.2 ± 3.3 years) were recruited into a self-selected intervention trial: 26 started with a GFD within a median of 38 days postonset, whereas 19 remained on a standard diet. The main outcomes were the decline in C-peptide area under the curve (AUC) in mixed-meal tolerance tests (MMTTs) at 6 and 12 months relative to 1 month after diabetes onset and the difference in insulin dose, insulin dose-adjusted A1c (IDAA1c) and HbA1c assessed every 3 months. The adherence to the GFD was verified by immunoreactive gluten in the stool and by food questionnaires at every visit. Quality of life (QoL) questionnaires were administered to the participants at the end of the intervention at 12 months. The data were analysed as per protocol (in 39 subjects who duly completed the whole follow-up: 20 in the GFD group, 19 in the control group) by linear and longitudinal regression models adjusted for sex, age and baseline variables. RESULTS: At 12 months, the difference in C-peptide AUC between subjects in the GFD group and controls was 205 pmol/L (95% CI -223 to 633; P = 0.34) in a model adjusted for age, sex and body weight, and for baseline insulin dose, MMTT C-peptide AUC and HbA1c assessed at 1 month after diagnosis. In a longitudinal analysis of all three time points adjusted for age, sex and body weight, C-peptide declined more slowly in the GFD group than in controls, with the difference in trends being 409 pmol/L/year (P = 0.04). The GFD group had a marginally lower insulin dose (by 0.15 U/kg/day; P = 0.07), a lower IDAA1c (by 1.37; P = 0.01) and a lower mean HbA1c (by 0.7% [7.8 mmol/mol]; P = 0.02) than those of the controls at 12 months. There was no appreciable difference between the groups in daily carbohydrate intake (P = 0.49) or in the QoL reported by the patients (P = 0.70) and their parents/caregivers (P = 0.59). CONCLUSIONS: A GFD maintained over the first year after type 1 diabetes diagnosis was associated with better HbA1c and a prolonged partial remission period. There was a hint of slower C-peptide decline but the association was not strong enough to make definite conclusions.
Keywords: Diet, Gluten-Free; beta-cell decline; Humans; remission.; dítě; Quality of Life; C-Peptide; Child; gluten-free diet; C-peptid; lidé; kvalita života; diabetes mellitus 1. typu; celiakie; bezlepková dieta; Insulin; Celiac Disease; C-peptide; inzulin; Diabetes Mellitus, Type 1; childhood type 1 diabetes